Diversification and fund performance: An analysis of buyout funds - Matthias Huss; Daniel Steger (Journal of Risk and Financial Management, 2020)
This paper studies the relationship between portfolio diversification and fund performance, based on an unexplored, hand-collected dataset of buyout funds. The dataset comprises detailed information at the level of portfolio companies, which allows measuring the concentration of the fund portfolios towards individual companies, industrial, and geographical focus. Our results suggest that diversification within, but not across industries, associates with higher buyout fund performance. We do not find a significant relationship between geographical diversification and performance. These results partly contradict results documented in prior literature.
Keywords: 330; performance; buyout funds; diversification; systematic risk